International Yearbook of Futurism Studies. - Berghaus, Günter; Ilnytzkyj, Oleh S.; Imposti, Gabriella Elina; Lodder, Christina (International Yearbook of Futurism Studies ;, 2019)
The ninth volume of the International Yearbook of Futurism Studies is dedicated to Russian Futurism and gathers ten studies that investigate the impact of F.T. Marinetti's visit to Russia in 1914; the neglected region of the Russian Far East; the artist and writers Velimir Khlebnikov, Vasily Kamensky, Maria Siniakova and Vladimir Mayakovsky; the artistic media of advertising, graphic arts, cinema and artists' books.